High-Temperature Tolerance of Photosynthesis Can Be Linked to Local Electrical Responses in Leaves of Pea - Sukhov, Vladimir; Gaspirovich, Vladimir; Mysyagin, Sergey; Vodeneev, Vladimir (Frontiers in Physiology, 2017)
It is known that numerous stimuli induce electrical signals which can increase a plant’s tolerance to stressors, including high temperature. However, the physiological role of local electrical responses (LERs), i.e. responses in the zone of stimulus action, in the plant’s tolerance has not been sufficiently investigated. The aim of a current work is to analyze the connection between parameters of LERs with the thermal tolerance of photosynthetic processes in pea. Electrical activity and photosynthetic parameters in pea leaves were registered during transitions of air temperature in a measurement head (from 23 to 30°C, from 30 to 40°C, from 40 to 45°C and from 45 to 23°C). This stepped heating decreased a photosynthetic assimilation of CO2 and induced generation of LERs in the heated leaf. Amplitudes of LERs, quantity of responses during the heating and the number of temperature transition, which induced the first generation of LERs, varied among different pea plants. Parameters of LERs were weakly connected with the photosynthetic assimilation of CO2 during the heating; however, a residual photosynthetic activity after a treatment by high temperatures increased with the growth of amplitudes and quantity of LERs and with lowering of the number of the heating transition, inducing the first electrical response. The effect was not connected with a photosynthetic activity before heating; similar dependences were also observed for effective and maximal quantum yields of photosystem II after heating. We believe that the observed effect can reflect a positive influence of LERs on the thermal tolerance of photosynthesis. It is possible that the process can participate in a plant’s adaptation to stressors.